Family Farming: Pembuatan Pestisida Nabati Dari Daun Sirsak Untuk Pengendalian Hama Pada Tanaman Sayuran Di Desa Belo Kecamatan Palibelo Kabupaten Bima - Marsinah; Dewi Nur Anjani; Muhammad Wardhani (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2024)
The production of botanical pesticides using soursop leaves can effectively prevent and control various pests. One such pesticide, derived from plant-based materials like soursop leaves, contains active compounds such as annonain, tannins, and acetogenins. The objective of this initiative is to provide knowledge on the benefits and importance of environmentally friendly botanical pesticides, particularly at the household garden scale. The Food Security Agency (Dinas Ketahanan Pangan, DKP) of Bima Regency promotes family farming by utilizing household gardens to cultivate crops as a means of supporting food security. The methods employed in this activity include the production and application of soursop leaf-based botanical pesticides, observation, harvesting, and evaluation of program success. This initiative is crucial for achieving optimal results in pest prevention and control. Currently, many farmers rely heavily on chemical pesticides, which pose significant risks to living organisms and the surrounding environment. The application of chemical pesticides often leaves harmful residues on plants and soil. Through the use of botanical pesticides, this program aims to provide a safer and more sustainable alternative for pest management.